Reduced intensity conditioning allogeneic stem cell transplantation for adult patients with acute lymphoblastic leukemia: a retrospective study from the European Group for Blood and Marrow Transplantation - Mohamad Mohty; Myriam Labopin; Reza Tabrizzi; Niklas Theorin; Axel A Fauser; Alessandro Rambaldi; Johan Maertens; Shimon Slavin; Ignazio Majolino; Arnon Nagler; Didier Blaise; Vanderson Rocha (Haematologica, 2008)
This retrospective study reported the outcome of 97 adult acute lymphoblastic leukemia patients who received a reduced-intensity conditioning allogeneic stem cell transplantation. With a median follow-up of 2.8 years, two year overall-survival, leukemia-free survival and non-relapse mortality were significantly better in patients transplanted in first complete remission (CR1, 52±9%; 42±10%; and 18±7% respectively) compared with those transplanted in more advanced phase (p=0.003, p=0.002 and p=0.01 respectively). In multivariate analysis, disease status (CR1 vs. advanced; p=0.001) and chronic graft-vs-host disease (p=0.01) were associated with an improved overall-survival, suggesting that reduced-intensity conditioning allogeneic stem cell transplantation is feasible in patients with high risk lymphoblastic leukemia in remission at transplantation.